What features of drug treatment programs help, or not, with access? a qualitative study of the perspectives of family members and community-based organization staff in Atlantic Canada - Holly Mathias; Lois A. Jackson; Jane A. Buxton; Anik Dubé; Niki Kiepek; Fiona Martin; Paula Martin (Substance Abuse Treatment, Prevention, and Policy, 2024)
Abstract Background Withdrawal management and opioid agonist treatment (OAT) programs help to reduce some of the harms experienced by people who use substances (PWUS). There is literature on how features of drug treatment programs (e.g., policies and practices) are helpful, or not helpful, to PWUS when seeking access to, or in, treatment. There is, however, relatively little literature based on the perspectives of family members/family of choice of PWUS and community-based organization staff within the context of Atlantic Canada. This paper explored the perspectives of these two groups on what was helpful, or not, about drug treatment programs in Atlantic Canada in terms of supporting access to, and retention in, treatment. Methods One-on-one qualitative telephone interviews were conducted in 2020 with the two groups. Interviews focused on government-funded withdrawal management and OAT programs. Data were coded using a qualitative data management program (ATLAS.ti) and analyzed inductively for key themes/subthemes using grounded theory techniques. Results Fifteen family members/family of choice and 16 community-based organization staff members participated (n = 31). Participants spoke about features of drug treatment programs in various places, and noted features that were perceived as helpful (e.g., quick access), as well as not helpful (e.g., wait times, programs located far from where PWUS live). Some participants provided their perceptions of how PWUS felt when seeking or accessing treatment. A number of participants reported taking various actions to help support access to treatment, including providing transportation to programs. A few participants also provided suggestions for change to help support access and retention such as better alignment of mental health and addiction systems. Conclusions Participants highlighted several helpful and not helpful features of drug treatment programs in terms of supporting treatment access and retention. Previous studies with PWUS and in other places have reported similar features, some of which (e.g., wait times) have been reported for many years. Changes are needed to reduce barriers to access and retention including the changes recommended by study participants. It is critical that the voices of key groups, (including PWUS) are heard to ensure treatment programs in all places support access and retention.